Location Models with Multy Criterious Networks (Case Study: The Industrial of Rice Processing in The Batubara District) - Gultom, Parapat; Nababan, Esther Sorta Mauli; Marpaung, Jonathan Liviera (Journal of Research in Mathematics Trends and Technology, 2022)
Determining location is a problem encountered in many areas of everyday life. Determining this location becomes complex when many factors are taken into consideration, where one factor and another can conflict. One of the issues that will be discussed in this research is determining the location of the rice processing industry. This problem needs to be studied considering that the opportunity to establish a rice industry in several regions in Indonesia is very high considering that the potential for the main raw material (rice) is very large, as is the rice market where the largest population of the Indonesian nation makes rice the main food ingredient. The case study that will be discussed in this research is the rice processing industry in Batu Bara Regency. Batu Bara Regency is one of the districts/cities in North Sumatra Province which has enormous rice potential. In order to improve the welfare of farmers and provide good quality rice for the community, a Rice Processing Industry is needed. The problem in the rice processing industry is very complex, apart from the seasonal availability of rice raw materials, is the location where the rice processing factory is located. Various criteria need to be considered in this determination relating to the distance of the rice processing industry factory to each source of the main raw material (rice). Determining this location is very complex because it involves multiple criteria. This research will provide a location determination model using a Multi Criteria Network. The criteria used to determine the location of the rice processing industry in Batu Bara Regency are the transportation distance from the raw material center, travel time, and the condition of the road connecting the raw material center to the factory location. Based on the criteria for distance between rice centers and rice processing industrial factories, a route with a total minimum distance score of 0.71 is obtained. Meanwhile, based on travel time, the best route was obtained with a minimum total time score of 1.61. Based on the quality of the road taken, the best route was obtained with a maximum total score of 0.25. By considering the three criteria, the best route was obtained with a total optimum score of 2.96.